PENGGUNAAN MODEL PEMBELAJARAN COPERATIVE LEARNING TIPE STAD PADA PEMBELAJARAN IPS DI SEKOLAH DASAR - Sari, Ike Yuni; Nasrul, Nasrul; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThe background of this research study low yields Elementary School fourth grade students. The purpose of this study is to describe the application STAD type Cooperative Learning learning model to improve learning outcomes of students of class IV SDN 13 Cingkariang Banuhampu. This type of research is the Classroom Action Research using qualitative and quantitative approaches. Subjects were practitioner and teacher Elementary School fifth grade students numbered 21 people. The results showed an increase in student learning outcomes of the first cycle that 77 (enough) to the second cycle is 90 (very good). Thus, the application of STAD type Cooperative Learning learning model to improve learning outcomes fourth  grade students of SDN 13 Cingkariang Kecamatan Banuhampu.Key Word: Learning outcomes, STAD type Cooperative Learning learning model